Análise da contribuição da protensão à resistência ao cisalhamento em vigas pré-fabricadas de concreto protendido - Avelino, Jeyce Nielle Câmara (2021)
This research aimed to study the collaboration of prestressing in the shear-resistant capacity of prefabricated prestressed concrete beams, through literature review and analysis of beams of different heights and concrete compressive strength ranging from 35 to 90MPa. In addition, the influence of the design of prestressing strands (straight or polygonal) and their quantity on the collaboration of complementary mechanisms to the truss in the region of maximum tangential stresses was also evaluated. This parametric analysis of the effect of prestressing on shear strength was performed under the criteria of NBR 6118:2014, EUROCODE 2:2004 and ACI 318:2019 standards. As a result, it was observed that this effect was considered more intensely by the American standard ACI 318:2019, followed by NBR 6118:2014 and EUROCODE 2:2004. For all groups, the increase in the prestressing contribution of the 60 cm-height beam to the 100 cm-height beam was greater than that of the 80-cm beam to the 100 cm beam, and, in general, the contribution to the increase in strength to shear was decreasing as the compressive strength of concrete increased. Both facts are mainly due to the decrease in the compressive stress in the concrete (less prestressing force applied due to the smaller amount of prestressed reinforcement needed), since the inertia of the section increased significantly while the loading remained practically the same, changing only the portion due to own weight. Finally, the 20% increase in the steel area caused the portion of the prestressing contribution to increase on average 22% for NBR 6118:2014, 6.22 % for ACI 318:2019 and 29.1% for EUROCODE 2:2004. These results demonstrate that the American standard considers little or nothing, in the case of the approximate method, the steel area in its calculation process, while the Brazilian and European standards consider this influence in a relevant way.